Free dissociable IGF-I: Association with changes in IGFBP-3 proteolysis and insulin sensitivity after surgery. Issue 2 (April 2016) - Bang, Peter; Thorell, Anders; Carlsson-Skwirut, Christine; Ljungqvist, Olle; Brismar, Kerstin; Nygren, Jonas
Summary: Background: Patients receiving a carbohydrate drink (CHO) before major abdominal surgery display improved insulin sensitivity postoperatively and increased proteolysis of IGFBP-3 (IGFBP-3-PA) compared to patients undergoing similar surgery after overnight fasting. Aims: We hypothesized that serum IGFBP-3-PA increases bioavailability of circulating IGF-I and preserves insulin sensitivity in patients given CHO. Design: Matched control study. Methods: At Karolinska University Hospital, patients given CHO before major elective abdominal surgery (CHO, n = 8) were compared to patients undergoing similar surgical procedures after overnight fasting (FAST, n = 10). Results from two different techniques for determination of free-dissociable IGF-I (fdIGF-I) were compared with changes in IGFBP-3-PA and insulin sensitivity. Results: Postoperatively, CHO displayed 18% improvement in insulin sensitivity (hyperinsulinemic clamp) and increased IGFBP-3-PA vs. FAST. As determined by IRMA, fdIGF-I increased by 48 ± 25% in CHO while fdIGF-I decreased by 13 ± 18% in FAST (p < 0.01 vs. CHO, when corrected for duration of surgery). However, fdIGF-I determined by ultra-filtration decreased similarly in both groups (−22 ± 8% vs. −25 ± 8%, p = 0.8) and IGFBP-1 increased similarly in both groups. Patients with less insulin resistance after surgery demonstrated larger increases in fdIGF-I by IRMA (r = 0.58, p < 0.05). Fifty-three % of the variability of the changes in fdIGF-I by IRMA could be explained by changes in IGFBP-3-PA and total IGF-I levels (p < 0.05), while IGFBP-1 did not contribute significantly. Conclusion: During conditions when serum IGF-I bioavailability is regulated by IGFBP-3 proteolysis, measurements of fdIGF-I by IRMA is of physiological relevance as it correlates with the associated changes in insulin sensitivity.